الدوافع التي تدفع الشباب الجامعي الى التطوع في الحشد الشعبي من وجهة نظرهم - جابر هاشم, أميرة (جامعة الوادي University of Eloued, 2017)
يهدف البحث الى الكشف عن الدوافع التي تدفع الشباب في التطوع في الحشد الشعبي من وجهة نظر طلاب جامعة الكوفة في محافظة النجف الاشرف ، ومعرفة الفروق في الدوافع التي تدفع الشباب في التطوع في الحشد الشعبي وفقا للتخصص الدراسي ، وتكّونت عينة البحث من (260) طالبا ، وللدوام الصباحي للعام الدراسي 2015-2016 ، تم اختيارهم بالطريقة العشوائية البسيطة ، ولتحقيق هدفا البحث ، تم بناء استبيان للأسباب التي تدفع الشباب في التطوع في الحشد الشعبي متكون من ستة مجالات هي : ( الدينية ، الاقتصادية ، السياسية ، الوطنية ، النفسية والشخصية ، الاجتماعية ) ، ، كشفت نتائج البحث عن الدوافع التي تدفع الشباب في التطوع في الحشد الشعبي من وجهة نظر طلاب الجامعة مرتبة حسب أهميتها ، مجال الدوافع الدينية حصل على المرتبة الاولى ، ومجال الدوافع الوطنية حصل على المرتبة الثانية ، ومجال الدوافع الاقتصادية حصل على المرتبة الثالثة ، ومجال الدوافع النفسية والشخصية حصل على المرتبة الرابعة ، ومجال الدوافع السياسية حصل على المرتبة الخامسة ، مجال الدوافع الاجتماعية حصل على المرتبة السادسة ، وتبين عدم وجود فرق في الدوافع التي تدفع الشباب الجامعي للتطوع في الحشد الشعبي من وجهة نظرهم وفقا متغير التخصص الدراسي ، وتقدمت الباحثة بمجموعة من التوصيات والمقترحات . The research aims to reveal the motives that push young people about volunteering popular crowd from the views point of Kufa University students in the province of Najaf, and know of the differences in the motives why people volunteer some popular crowd according to a Academic Specialization, The sample of the research(260 students), Day shift for the academic year 2015-2016 , have been chosen simple randomly, To achieve the two goals of search, Questionnaire was built for the motives that push young people about volunteering popular crowd composed of six areas:(Religious, economic, political, national, psychological and personal, social), After checking the reliability of the psychometric properties of the questionnaire, It has been applied to a sample search , It revealed the search for causes that drive young people towards volunteering popular crowd from the perspective of university students in order of importance Results, The field of religious The motives got the first place, and the area of national The motives got the second place, and for economic The motives got third place, and the mental and personal The motives, got the fourth place, and the field of political The motives got the fifth place, the field of social causes earned a sixth place, And it found no difference in the causes that drive university students to volunteer the popular crowd from their point of view according to a variable Academic Specialization, The researcher made a set of recommendations and proposals.
مقال
Keywords: الدوافع ؛ التطوع ؛ الحشد الشعبي; The motives; Volunteerism; the popular crowd